Strategies Used by Islamic Religious Education Teachers in Character Building Among Students at State Junior High School 12, South Konawe - Irma Nurfatimah; Evarial, Irwan (Dirasah: Jurnal Pendidikan Islam, 2026)
This study aims to identify the strategies used by Islamic Religious, Education (PAI) teachers in fostering students’ morality at SMP Negeri 12 Konawe Selatan, to describe the formas of mora ldevelopment impelemnted, and to analyze the supporting and inhibiting factors. This research employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation. The data analysis technique consisted of three stages: data reduction, data display, and conclusion drawing or verification.  To ensure data validty, the researcher applied source triangulation, technique triangulation, and time triangulation to obtain objective and reliable findings. The findings show that PAI teachers apply several strategies, including exemplary modeling, giving advice, habituating students to attend Dzuhur prayer in congregation, collaborating with school counselors and other staff, and involving parents.  Forms of moral development include respect for teachers, discipline, honesty, participation in religious activities, and preventing bullying behavior. Supporting factors include collaboration ith parents and cooperation among teachers. Inhibiting factors include limited instructional time for Islamic Religious Education, and low student awareness of the importance of moral education. This study is expected to serve as an evaluation reference for PAI teachers and school in designing more effective and sustainable moral development strategies. The novelty of this research compared to previous studies on PAI teachers’ strategies lies in its focus on examining the strategies of Islamic Religious Education (PAI) teachers in fostering students’ moral character through exemplary behavior, advice strategies, habituation of congregational Dhuhr prayer, collaboration with counseling teachers and school authorities, as well as parental involvement in students’ moral development at SMP Negeri 12 Konawe Selatan. This study also specifically discusses moral development related to student behaviors such as lack of respect for teachers, truancy, non-participation in religious activities, dishonesty, and bullying behavior found within the school environment.